On the Optimization of the Microstructure and Mechanical Properties of Al-Co-Cr-Cu-Fe-Ni-Ti –Based High Entropy Alloys - A.M. Manzoni; S. Singh; H.M. Daoud; R. Völkl; U. Glatzel; N. Wanderka (Jordan Journal of Physics, 2025)
Widely investigated AlCoCrCuFeNi high entropy alloy has been chosen for optimization of the microstructural and mechanical properties. Different paths have been chosen for optimization; namely the decrease of segregating element Cu, the increase of oxidation protective elements Al and Cr and the approach towards a γ-γ’ microstructure as in Ni-based superalloys. Microscopical observation has been made for each optimization step and compared with results obtained by Vickers microhardness measurements. Out of five derivate alloys: AlCoCrFeNi, Al23Co15Cr23Cu8Fe15Ni16, Al8Co17Cr17Cu8Fe17Ni33, Al8Co17Cr14Cu8Fe17Ni33Mo1Ti1W1 and Al10Co25Cr8Fe15Ni36Ti6, the most promising one has been chosen for further investigation. Keywords: High entropy alloys; Microstructure; Transmission electron microscopy.